In vitro assessment of oat β-glucans nutritional properties: An inter-laboratory methodology evaluation. (15th November 2018) - Kock, Lindsay B.; Brummer, Yolanda; Exley, Tracy; Rhymer, Camille; Storsley, Joanne; Xie, Kenny; Chu, YiFang; Ou, Boxin; Ames, Nancy P.; Tosh, Susan M.; Bordenave, Nicolas
Highlights: An in vitro digestion method for assessing β-glucans functionality was tested. A 4-lab collab design was used to assess the accuracy and precision of the method. The in vitro digestion step significantly increased measurement uncertainty. Areas of improvement and standardization were identified. Abstract: The purpose of this inter-laboratory study was to test the repeatability and reproducibility of an in vitro method aimed at analyzing the physicochemical properties under physiological conditions of β-glucans from foods. After evaluating β-glucans molar mass and quantification methods using five β-glucan controls, four laboratories ran six oat-based products through in vitro digestion, measured β-glucans solubility and viscosity and molar mass of solubilized β-glucans. The determination of the molar mass of β-glucan controls, their viscosity in solution and β-glucans content in food samples exhibited relative standard reproducibility of 20.9–40.9%, 10.2–40.9% and 2.3–14.8%, respectively. After in vitro digestion, relative standard reproducibility ranged 12.1–60.0%, 12.2–64.3% and 9.7–36.3% for molar mass of extracted β-glucans, their viscosity and their solubility, respectively. Although the characterization methods were satisfactory within the limits of current technology, the in vitro extraction contributed significantly to the uncertainty of final characterization.